Aligning E-Learning and Knowledge Maturity for Institutional Success: A Functional Approach: Exploring the Impact of E-Learning on Institutional Success in Mauritius (Journal of Advances and Scholarly Researches in Allied Education, 2018)
E-Learning is described as a method of delivering information through a web-based platform via the internet. Many organizations namely training centers, private establishments and universities have fostered e-learning as a mode of teaching to complement the traditional class-room model or as a collaborative device. With the improvement of ICT infrastructure in Mauritius, technology is rapidly enhancing online learning to create a digital island. This has led to a dramatic increase in the use of e-learning platforms to deliver education in the nation. According to the statistics in the National ICT Strategic plan (NICTSP) of 2007-2011, Mauritius has an Internet penetration ratio of 29.6 with 380,000 internet users. Moreover, based on the Global Information Technology Report of 2008-2009, Mauritius is ranked 51st on the network readiness index.